Integrating Local Wisdom of Nek Pung Dance in Grade 4 Elementary School Science Learning - Asrial, Asrial; Syahrial, Syahrial; Sabil, Husni; Kurniawan, Dwi Agus; Novianti, Ulfah (Jurnal Penelitian dan Pembelajaran IPA, 2022)
Currently, local wisdom is getting eroded. Local wisdom is a habit of the local community that has noble values so that efforts need to be made to preserve it, such as the local wisdom of the nek pung dance in Jambi province, Indonesia. This paper aimed to analyze the local wisdom of the nek pung dance and the educational curriculum to be linked and integrated into science learning. This study uses a qualitative approach by collecting natural information from several sources, namely traditional leaders, community leaders, education and culture offices, and elementary school teachers. In addition, researchers also analyzed educational curriculum documents, teacher books, and student books. The results analysis showed the that local wisdom of the nek pung dance can be integrated into grade 4 on theme I the beauty of togetherness, sub-theme I cultural diversity of my people, in learning 1 which includes science competency as one of the competencies.